Madras Studios : Narrative, Genre, and Ideology in Tamil Cinema - Pillai, Swarnavel Eswaran (Sage Publications Pvt. Ltd, 2015)
This study of Tamil cinema is among the few works in English on South Indian cinema in the studio era.